Experimental Implementation of Cascaded H-Bridge Multilevel Inverter with an Improved Reliability for Solar PV Applications - C. Dhanamjayulu; T. Girijaprasanna (International Transactions on Electrical Energy Systems)
This study presents the boost converter-based cascaded H-bridge (CHB) multilevel inverter with improved reliability for solar PV (photovoltaic) applications. The solar PV is associated with the boost converter to enhance DC link voltage by using the maximum power point tracking-perturb and observe (MPPT-P & O) technique. The proposed configuration is aimed toward the performance analysis of the boost converter-based CHB MLI by reducing the number of components, low total harmonic distortion (THD), reduced power, less cost function, low total standing voltage (TSV), improved reliability, and switching losses for solar PV application. In this study, a CHB multilevel inverter is used to obtain stepped pure sinusoidal AC from the solar PV array. The proposed boost converter extracts maximum power and enhances higher DC link voltage which provides high efficiency. The boost converter is integrated with a 27-level CHB multilevel inverter to generate near-sinusoidal output voltage with lower THD. The inverter is tested with linear and nonlinear loads for robustness, and during dynamic loads, inverter is stable and well suited to grid-connected applications. A detailed comparison is presented on the component count and reliability aspects with existing MLIs and 27-level MLIs. The simulation outcomes of the implemented arrangement are presented with the help of MATLAB/Simulink, an experimental prototype is developed using a dSPACE RTI1104 controller and also tested in the research laboratory for checking the possibility of the implemented arrangement.